A retrospective study of bevacizumab for treatment of brainstem glioma with malignant features. (January 2018) - Moriya, Shigeta; Ohba, Shigeo; Adachi, Kazuhide; Nishiyama, Yuya; Hayashi, Takuro; Nagahisa, Shinya; Kaito, Takafumi; Nakae, Shunsuke; Hirose, Yuichi
Highlights: Bevacizumab might be a potential therapeutic option for brainstem glioma. The Karnofsky performance status improved from 56.7 to 71.7 on average. The median progression-free survival after bevacizumab administration was 7 months. The median overall survival after diagnosis was 16.5 months. Abstract: Brainstem glioma is impossible to resect completely, and patients with this type of glioma show a poor prognosis. Therefore, a more effective adjuvant therapy is required to prolong survival. Bevacizumab is an endothelial growth factor monoclonal antibody with strong anti-vascular effects, which may suppress tumor progression. We performed a retrospective study of data from 6 patients with brainstem glioma showing malignant features who were treated with bevacizumab. Tumor-associated lesions, as evaluated by T2 weighted or fluid-attenuated inversion-recovery magnetic resonance imaging, were reduced in all patients, although the timing of the start of bevacizumab administration and pretreatment were not uniform. Clinical symptoms improved in 4 patients and progression was inhibited in 2 patients. The Karnofsky performance status improved from 56.7 to 71.7 on average. The median reduction ratio of tumor-associated lesions was 76.3%, but tumor suppression did not last in any of the cases. Furthermore, 5 patients died of tumor progression, and 1 patient died of a complication of necrotizing colitis. The median progression-free survival after bevacizumab administration was 7 months. The median overall survival after diagnosis was 16.5 months. Bevacizumab might be a potential therapeutic option for progressive brainstem gliomas with malignant features.